2013
DOI: 10.1242/dev.080531
|View full text |Cite
|
Sign up to set email alerts
|

Endoreplication and polyploidy: insights into development and disease

Abstract: SummaryPolyploid cells have genomes that contain multiples of the typical diploid chromosome number and are found in many different organisms. Studies in a variety of animal and plant developmental systems have revealed evolutionarily conserved mechanisms that control the generation of polyploidy and have recently begun to provide clues to its physiological function. These studies demonstrate that cellular polyploidy plays important roles during normal development and also contributes to human disease, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
336
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(351 citation statements)
references
References 113 publications
(105 reference statements)
8
336
1
6
Order By: Relevance
“…Therefore, the duplicated chromosomes produced by endoreplication may be packed into separated nucleus, thus forming multinucleated cells. 1,27,34,42 Our results showed that most of the polyploid decidual cells are manifested as binucleated and arrested in G2/M phase, suggesting that endoreplication and M phase arrest may be the main mechanisms involved in decidual cell polyploidization. CDK1, also known as cell division control protein 2, controls the onset of mitotic phase.…”
Section: E2f8 Initiates the Endoreplication Of Mouse Decidual Cellsmentioning
confidence: 60%
“…Therefore, the duplicated chromosomes produced by endoreplication may be packed into separated nucleus, thus forming multinucleated cells. 1,27,34,42 Our results showed that most of the polyploid decidual cells are manifested as binucleated and arrested in G2/M phase, suggesting that endoreplication and M phase arrest may be the main mechanisms involved in decidual cell polyploidization. CDK1, also known as cell division control protein 2, controls the onset of mitotic phase.…”
Section: E2f8 Initiates the Endoreplication Of Mouse Decidual Cellsmentioning
confidence: 60%
“…Recent work suggests that pathological polyploidization is an adaptation to genomic stress (60). Cells respond to a diverse array of DNA lesions with an evolutionarily conserved DNA damage response (61).…”
Section: Resultsmentioning
confidence: 99%
“…In some circumstances, CKIs also promote a modified cell cycle known as endoreplication or endoreduplication, in which mitosis and cytokinesis are bypassed, but DNA replication continues, resulting in cells with increased ploidy. 1,2 The number of genome-encoded CKIs varies among different species and kingdoms, and some lineages have more than one distinct type of CKI. For example, mammals have 2 CKI families, CDK interacting protein/kinase inhibitory protein (CIP/KIP) and INHIBITOR of CDK4 (INK4) and these 2 families share no sequence similarity.…”
Section: Introductionmentioning
confidence: 99%